Empatia: atitude fundamental do professor do ensino superior estudo teórico sobre empatia e práticas pedagógicas no ensino superior - Carnizelo, Nicole Rodrigues (2019)
The purpose of this research is to investigate the influence of pedagogical practices of empathy in the relationship between teachers and students in facilitating the learning process of students of higher education. Through a qualitative approach, using bibliographic research and documents analysis, we intended to understand the meanings that the authors give to empathy by proposing a conceptualization of empathy in teaching. To unveil how empathy manifests itself in teaching practices in the teacher-student relationship and to understand how it influences learning, we conducted a survey of information from Ken Bain's book What do the best teachers do (2004), where we investigate and critically analyze several reports of teachers' attitudes that reflect an empathetic behavior in the teaching practice. We’ve expanded the research with the survey of other authors who worked on this theme, in particular Carl Rogers, in light of the conceptions of the Person Centered Approach, originated in clinical psychology and also applied in the educational field; Daniel Goleman and the studies of social intelligence, Brene Brown and her studies on courage, vulnerability, shame and empathy, Marcos Masetto in teaching, among others. The analysis of the texts allowed us to understand in greater depth the meanings that their authors give to empathy. We recognize that not all examples use the same language to describe pedagogical practices of empathy. However, as we evolved from research through the literature, the conceptualization of empathy helped us reveal in the terminologies and scenes described, commonplace practices, ways of thinking and acting that we recognize as patterns of empathy practice as they point to for the humanization of the teacher - student relationship with the understanding of the student 's perspective, of who he / she is, what he / she feels, his / her aspirations and how he / she learns, demonstrating trust in their learning capacity, stimulating a sense of security, freedom and motivation for the student knowledge as an instrument for facilitating learning